The Time Variation of Risk and Return in the Foreign Exchange and Stock Markets - Giovannini, Alberto; Jorion, Philippe (Journal of Finance, 1989)
This paper attempts to determine whether the fluctuations of conditional first and second moments—which are observed for many assets—are consistent with the Sharpe-Lintner-Mossin capital asset pricing model. We test the mean-variance model under several different assumptions about the time variation of conditional second moments of returns, using weekly data from July 1974 to December 1986, that include returns on a portfolio composed of dollar, Deutsche mark, sterling, and Swiss franc assets, together with the U.S. stock market. The results indicate that estimated conditional variances cannot explain the observed time variation of risk premia.